Probing and relating the morphology, structure and performance evolution of low pressure RO membranes under chlorine exposure. Issue 5 (October 2021) - You, Meng; Feng, Guangli; Fei, Pengfei; Zhang, Yufeng; Cao, Zhen; Xia, Jianzhong; Lau, Woei-Jye; Meng, Jianqiang
Abstract: The polyamide layer of reverse osmosis (RO) membrane is susceptible to chlorination degradation. Guidelines for validation and integrity monitoring of the low pressure RO (LERO) membrane morphology and performance upon chlorination is still rarely reported. In this study, we selected three commercial LERO membranes (i.e., LP, ULP and LCLE) to study their structure and separation performance change for exposing to chlorine under both pressurized and static chlorination conditions, with different active chlorine concentrations and pH. At the pressurized testing, the membrane water flux increased at the initial stage due to the decrease of water passage restriction by the destroy of the hydrogen bond in the polyamide, and then the water flux sharply decreased and gradually leveled off, which should be resulted from the destroy of chemical structure of polyamide and membrane compaction under high pressure. The salt rejection slightly changed, presumably due to the combination of tightening effect, compactness and defect plugging by foulants. As for the static chlorination test, active chlorine concentration and chlorination time were not unequivocalness at the same chlorination intensity. Higher active chlorine concentration could cause more serious chlorination degradation. Based on the water flux change at neutral pH and under static chlorination conditions, a flux reduction equation with active chlorine concentration was fitted by y = ax b (1＜x＜1000), which could help us to predict the water flux under a specific chlorine concentration and time. Graphical Abstract: ga1 Highlights: The chlorination of PA membrane was studied in pressurized and static conditions. The chlorination at pressurized condition was much severer than static condition. Membranes were severely destroyed under high chlorine content and acid medium. The role of chlorine concentration in chlorination was greater than exposure time. The water flux reduction with chlorine concentration can be fitted by an equation.